Intercultural interaction and communication at the Chinatown marketplace, Petak Sembilan, Indonesia - Julianto, Gregah Fajar; Ridaryanthi, Melly (Penerbit Universiti Kebangsaan Malaysia, 2023)
Petak Sembilan is a Chinatown area located in Jakarta, where many Chinese hereditary communities stay. There is a famous Petak Sembilan Market that becomes the meeting point of mostly Chinese hereditary merchants with their customers. The interaction that occurred for years has always been interesting to be studied for the dynamic of their communication. The aim of this study is to identify the intercultural communication and interaction patterns between customers and merchants who are culturally diverse. The verbal and nonverbal communication were addressed in their interactions. This research employed a qualitative approach with a case study method. Data collection techniques used were observation, interview, and documentation for literature review. The results of the study are presented in the form of descriptive writing. The findings show that intercultural communication that occurred between the merchants and customers is a linear two-way communication. Verbal and nonverbal cues were identified from the observation conducted. During the interaction, the merchant and customers tend to use the same language to avoid misunderstanding.